ISOLATION AND CHARACTERIZATION OF AN AZO DYE REACTIVE RED 2 DEGRADING BACTERIA FROM DYE CONTAMINATED SOIL - MALLIKARJUN C. BHEEMARADDI; CHANNAPPA T. SHIVANNAVAR; SUBHASCHANDRA M. GADDAD (International Journal of Pharma and Bio Sciences, 2013)
A bacterial strain GSM3, capable of decolorizing an azo dye Reactive Red 2 was isolated from dye contaminated soil sample collected from Ammu dyeing industry, Bellary, India. Based on phenotypic characteristics and 16S rDNA sequencing, strain GSM3 was identified as Pseudomonas aeruginosa GSM3. Isolate GSM3 showed 97% decolorization of Reactive Red 2 (300 mgLâ”€1) within 10 h, while maximally it could decolorize 2 gLâ”€1 of dye within 62 h with 75% decolorization in carbon free mineral salts medium supplemented with 0.1% (w/v) of yeast extract as a cosubstrate under static condition. The isolate has shown good decolorization activity over a wide range of pH from 5.0 to 9.0 and temperature 30oC to 45oC respectively. However, highest decolorization was observed at 37oC and pH 7.0. UV-vis analyses and colorless bacterial cells suggested that the isolate GSM3 exhibited decolorizing activity through biodegradation, rather than inactive surface adsorption.Thus, the isolate GSM3 had great potential to be applied in biodegradation of dye effluents treatment.